PELATIHAN PROBLEM SOLVING BERBASIS WEB SEBAGAI UPAYA PENCEGAHAN MASALAH KESEHATAN MENTAL PADA MAHASISWA - Siti Khadijah; Satino; Yuyun Setyorini; Yopi Harwinanda; Rendi Editya Darmawan (LPPM Universitas dr. Soebandi, 2023)
Mental health is very important in student life, if the soul is not healthy, the quality of life will be reduced and have an impact on academics. The prevalence of mental health problems is high especially anxiety as well as depressive disorders, and only a small percentage of college students receive treatment because of stigma. Internet interventions have proven effective for mental health treatment. The purpose of this community service is to increase knowledge and skills in operationalizing web-based problem solving in order to prevent mental health problems in students. The method is by providing training via zoom, pre and post tests, and this activity is carried out on lecturers and first-year students in all Departments of Surakarta Health College with a total of 699 in training received two materials; The first, the importance of PA counseling guidance in universities with speakers from Universitas Airlangga, the second material is web-based problem solving socialization speakers from the community service team. The results showed a significant difference in .000 operational ability and 75% student satisfaction after studying academic guidance using problem solving web.